2020
DOI: 10.5897/ajbr2019.1070
|View full text |Cite
|
Sign up to set email alerts
|

Vitellaria paradoxa fruit pulp bioethanol production potential: A review

Abstract: In the last decade, bioethanol has become a powerful biofuel for the improvement of environmental pollution such as reduction in greenhouse gas levels. Yet, the source and type of substrate material plays a crucial role in the bioethanol production process due to the different compositional characteristics and availability of monomeric sugars. Different substrates of first, second and third generation fuel sources exist and may be used as reliable and sustainable substrates for bioethanol generation. The curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Shea nut survives in areas with 400‐ to 800‐mm yearly rainfall across the African continent and grows naturally from West Africa through to East Africa to the Ethiopian highlands, 8 while Nigeria and Ghana have large acreages of the shea nut tree. Although shea nut fruit is used in the food industry, soap making, and health care, obtaining accurate production data for shea nut fruit is challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shea nut survives in areas with 400‐ to 800‐mm yearly rainfall across the African continent and grows naturally from West Africa through to East Africa to the Ethiopian highlands, 8 while Nigeria and Ghana have large acreages of the shea nut tree. Although shea nut fruit is used in the food industry, soap making, and health care, obtaining accurate production data for shea nut fruit is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…6 Phuang et al studied WT of yard waste to improve its properties as an energy resource with reaction temperature and the water-to-biomass (W/B) ratio between 180 and 220 C and 10:1-30:1 respectively and showed that energy yields were in the range of 63.9%-74.4%. 7 Shea nut survives in areas with 400-to 800-mm yearly rainfall across the African continent and grows naturally from West Africa through to East Africa to the Ethiopian highlands, 8 while Nigeria and Ghana have large acreages of the shea nut tree. Although shea nut fruit is used in the food industry, soap making, and health care, obtaining accurate production data for shea nut fruit is challenging.…”
Section: Introductionmentioning
confidence: 99%